PLEKHA5 regulates the survival and peritoneal dissemination of diffuse-type gastric carcinoma cells with Met gene amplification - Yuko Nagamura; Makoto Miyazaki; Yoshiko Nagano; Masako Yuki; Kiyoko Fukami; Kazuyoshi Yanagihara; Kazuki Sasaki; Ryuichi Sakai; Hideki Yamaguchi (Oncogenesis, 2021)
Abstract Met gene amplification has been found in a subset of malignant carcinomas, including diffuse-type gastric carcinoma (DGC), which has a poor prognosis owing to rapid infiltrative invasion and frequent peritoneal dissemination. Met is considered a promising therapeutic target for DGC. However, DGC cells with Met gene amplification eventually acquire resistance to Met inhibitors. Therefore, identification of alternate targets that mediate Met signaling and confer malignant phenotypes is critical. In this study, we conducted a phosphoproteomic analysis of DGC cells possessing Met gene amplification and identified Pleckstrin Homology Domain Containing A5 (PLEKHA5) as a protein that is tyrosine-phosphorylated downstream of Met. Knockdown of PLEKHA5 selectively suppressed the growth of DGC cells with Met gene amplification by inducing apoptosis, even though they had acquired resistance to Met inhibitors. Moreover, PLEKHA5 silencing abrogated the malignant phenotypes of Met-addicted DGC cells, including peritoneal dissemination in vivo. Mechanistically, PLEKHA5 knockdown dysregulates glycolytic metabolism, leading to activation of the JNK pathway that promotes apoptosis. These results indicate that PLEKHA5 is a novel downstream effector of amplified Met and is required for the malignant progression of Met-addicted DGC.